The role of corporate culture in suppressing discriminating practices against women's careers - Hendratmoko; Wijaya, Teddy (Business and Entrepreneurship Department, Kwik Kian Gie School of Business and Information Technology, Jakarta, 2023)
A career is an individual's journey to achieve a better goal. Corporate culture is an important thing that a company must have. Discrimination is common in heterogeneous communities. This study aims to understand corporate culture's role in efforts to suppress discriminatory practices against women's careers. This study used a descriptive qualitative approach. This study used three informants who worked at PT. KE Farmasi in North Jakarta. In addition to secondary data, this study also used primary data from interviews with informants. The results of this study show that there are still discriminatory practices against women's careers in companies. Prejudice and stereotypes are one of the reasons why discriminatory practices still occur against women's careers. Performance-based corporate culture is one way to avoid discriminatory practices against women's careers. This research is expected to contribute to the importance of performance-based corporate culture.